2019
DOI: 10.1016/j.jenvp.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Measuring pro-environmental behavior: Review and recommendations

Abstract: Any scientific attempt to understand, predict, or promote pro-environmental behavior requires an adequate measurement tool for the assessment of pro-environmental behavior. The multidisciplinary interest in pro-environmental behavior has generated a large variety of such tools, ranging from domain-general and domain-specific self-report measures, field observations conducted with the help of informants, trained observers, or technical devices, to behavioral tasks for use in the laboratory. The present review d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
330
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 507 publications
(343 citation statements)
references
References 113 publications
(106 reference statements)
4
330
0
9
Order By: Relevance
“…Definitions of pro‐environmental behaviour are often broad and vary within the literature (as noted by Lange & Dewitte, ). However, for the purposes of the study, pro‐environmental behaviour was defined as those behaviours that proactively attempted to conserve and/or protect the natural environment (Stern, ; Vlek & Steg, ).…”
Section: Methodsmentioning
confidence: 99%
“…Definitions of pro‐environmental behaviour are often broad and vary within the literature (as noted by Lange & Dewitte, ). However, for the purposes of the study, pro‐environmental behaviour was defined as those behaviours that proactively attempted to conserve and/or protect the natural environment (Stern, ; Vlek & Steg, ).…”
Section: Methodsmentioning
confidence: 99%
“…A limitation of our study is that environmental behaviors were self-reported, rather than objectively measured (Kormos & Gifford, 2014;Lange & Dewitte, 2019). Another limitation is that we relied on a single decision paradigm, the "give some" public goods game, and replications using other types of social dilemmas could point to possible boundary conditions of the reported effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, pro-environmental consumption behavior has been receiving increasing attention in the literature (Lacroix, 2018;Lange & Dewitte, 2019;Mainieri et al, 1997;Maio & Wei, 2013;Moser, 2015;Steinhorst & Klöckner, 2018;Urban et al, 2019;Welsch & Kühling, 2009). This focus is consistent with an increasingly broader interest in understanding pro-environmental behavior that has persisted for several decades (e.g., Hines et al, 1987;Kollmuss & Agyeman, 2002;Lange et al, 2018).…”
Section: Pro-environmental Consumption Behaviormentioning
confidence: 99%